(untitled) (Bangladesh Journal of Microbiology, 2008)
A field experiment was conducted at the research farm of Bangabandhu Sheikh Mujibur Rahman Agricultural University (BSMRAU), Gazipur, Bangladesh to study the response of five chickpea (Cicer arietinum L) varieties to Rhizobium inoculant and mineral nitrogen on nodulation, nitrogen fixation, dry matter production, nitrogen (N) uptake, yield and quality of the crop. Among the treatments, Rhizobium inoculant in combination with Barichola-5 in absence of nitrogen performed best in recording number and dry weight of nodules and nitrogenase activity of chickpea. Barichola-2 in presence of 100 kg N/ha performed best in recording dry weight of shoot and root, number of branches, chlorophyll a and b, nitrogen content in shoot, nitrogen uptake by shoot, protein content in seed, number of seeds per plant, number of pods per plant, 1000-seed weight and stover and seed yields. The performances of Barichola-5 and Barichola-3 in presence of Rhizobium inoculant and in the absence of mineral nitrogen were comparable to Barichola-2 in most of the parameters of the crop studied. Keywords: Rhizobium inoculant, Nitrogen, Chickpea DOI: http://dx.doi.org/10.3329/bjm.v24i2.1261 Bangladesh J Microbiol, Volume 24, Number 2, December 2007, pp 146-150 DOI: http://dx.doi.org/10.3329/bjm.v24i2.1260